Early Electroencephalography Findings in Cardiogenic Shock Patients Treated by Venoarterial Extracorporeal Membrane Oxygenation. Issue 5 (May 2018) - Sinnah, Fabrice; Dalloz, Marie-Amélie; Magalhaes, Eric; Wanono, Ruben; Neuville, Mathilde; Smonig, Roland; Radjou, Aguila; Mourvillier, Bruno; Bouadma, Lila; Timsit, Jean-François; d'Ortho, Marie-Pia; Rouvel-Tallec, Any; et al.
Abstract : Objectives: We aimed to assess early electroencephalography findings in patients treated by venoarterial extracorporeal membrane oxygenation and their association with neurologic outcome. Design: Single-center observational study. Setting: Medical ICU of a university hospital. Patients: An early standardized electroencephalography assessment, that is, standard electroencephalography followed by continuous electroencephalography, was performed in consecutive cardiogenic shock patients requiring venoarterial extracorporeal membrane oxygenation. Associations between electroencephalography findings and outcome, defined as a composite of acute brain injury or death at 14 days, were investigated. Measurements and Main Results: Twenty-two patients with a median Full Outline of Unresponsiveness score of 4 (interquartile range, 3–6) were studied. Pupillary light reflex, corneal reflex, and cough reflex were preserved in 20 (90%), 17 (77%), and 17 (77%) patients, respectively. Overall, standard electroencephalography findings consisted of diffuse slowing in 21 patients (95%) and severe background abnormalities in 13 patients (59%) (i.e., a discontinuous [ n = 5; 23%] and/or an unreactive background [ n = 9; 41%]). Severe background abnormalities on standard electroencephalography (poor outcome rate: 69% vs 22%; p = 0.03) and absence of sleep transients on continuous electroencephalography (poor outcome rate: 67% vs 14%; p = 0.02) were associated with a poor outcome, whereas neurologic findings and doses of sedation were not. Patients without sleep transients on continuous electroencephalography tended to have lower Full Outline of Unresponsiveness scores than patients with preserved sleep transients-appearing patterns. Conclusions: In patients treated by venoarterial extracorporeal membrane oxygenation, early severe background abnormalities on standard electroencephalography provide important information on neurologic outcome. The lack of sleep transients on continuous electroencephalography reflects the severity of brain dysfunction and might represent an additional prognostic marker. Abstract : Supplemental Digital Content is available in the text.